Idiopathic Pulmonary Arterial Hypertension Newly Diagnosed in Pregnancy with Anemia and Threatened Preterm Labor - Harumsari, Stefani; Rahardjo, Bambang; Prasetyorini, Nugrahanti; Dwijayasa, Pande Made; Yogibuana, Valerinna; Rohman, Mohammad Saifur (Heart Science Journal, 2022)
Background: Pulmonary hypertension (PH) is a rare cardiovascular disorder that leads to right heart failure (RHF). Although most PH occurs secondary to congenital heart disease (CHD), PH can occur primarily due to pulmonary arterial vasculature abnormalities, known as Idiopathic pulmonary arterial hypertension (IPAH). In addition, the physiologic changes during pregnancy can potentially lead to worsening PAH and confer a poor prognosis. Therefore, when the mother refuses termination, a multidisciplinary team should manage the pregnancy and delivery to improve maternal and fetal outcomes.Objectives: This case report aimed to describe the importance of early diagnosis and treatment in PAH.Case reports: We reported a case of a 24-year-old woman with idiopathic pulmonary arterial hypertension (IPAH) that was newly diagnosed at 25 weeks of pregnancy and previously misdiagnosed with patent ductus arteriosus (PDA). This pregnancy was complicated with anemia and threatened preterm labor. Sildenafil was used as a vasodilator to reduce the symptoms of PAH. Unfortunately, the pregnancy was terminated at 29 weeks because of PPROM after considering giving lung maturation and neuroprotectant to the fetus. The patient was discharged without complication, but the baby died after eight days of intensive care due to HMD II, which led to respiratory failure.Conclusion: PAH in pregnancy is a life-threatening condition if untreated. Continuous treatments can help control the symptoms and avoid further complications for both mother and baby.